CD90 positive cells exhibit aggressive radioresistance in esophageal squamous cell carcinoma - Wang, Yuandong (J Thorac Dis, 2017)
BACKGROUND: Cancer stem cells (CSCs) are widely abundant and considered to be an important factor in therapy resistance. They are also promising potential targets for conquering tumors. We explored the effects of radiation on stem cell-like tumor cells via the candidate marker CD90 to provide new ideas for the comprehensive treatment of esophageal squamous cell carcinoma (ESCC). METHODS: We constructed CD90 overexpression ESCC cells by lentiviral transfection and observed differences of toxicity, proliferation, clone number, apoptosis, migration, invasion, and in vivo tumor formation after irradiation. RESULTS: We found that the population of CD90 positive cells showed CSC-like characteristics, including increased tumorigenicity and migration in ESCC cells. We discovered that these capacities were strengthened to varying degrees in remaining cells after irradiation. Further exploration revealed that the genes of ETS-1 and its downstream target MMPs changed significantly, which are correlated with the epithelial mesenchymal transition (EMT). These effects lead to enhanced tumor growth and resistance to radiation. CONCLUSIONS: We show that CD90 overexpressing ESCC cells exhibit CSC-like characteristics and radiation resistance. From a clinical perspective, ESCC patients with tumors that have high CD90 expression, which inhibits apoptosis, could exhibit more local invasion as well as distant metastasis, indicating a poorer prognosis. Research on the mechanism of CD90 may provide a new perspective to therapeutic strategies for patients with ESCC.